Nurses’ ability to function in an intercultural environment in light of their competenceand cultural intelligence - Brodowicz-Król, Magdalena; Kaczoruk, Monika; Malm, Maria; Skiba, Edyta; Chowaniec, Joanna (Nursing in the 21st Century, 2025)
Aim. Assessment of the relationship between cultural competences of the nursing staff , level of their cultural intelligence and the ability to participate eff ectively in intercultural interactions.Material and methods. The study included a group of 221 nurses and nurse practitioners, Standardised tools for the measurement of cultural intelligence - Cultural Intelligence Scale, and cultural competences - Cross-Cultural Competence Inventory). Statistical analyses were performed using the software Microsoft Excel 365, and Statistica 13.3. The level of significance was set at α=0.05.Results. A longer work experience was associated with higher lie scale scores, and the level of self-presentation decreased with nurses’ age. The level of cultural intelligence was high with respect to metacognitive intelligence while it was low regarding cognitive intelligence. The higher metacognitive intelligence, the higher the results obtained by the respondents according to the scales contributing to cultural competences, except for the scale concerning tolerance.Conclusions. It is necessary to continue studies assessing cultural competences of nurses, which may constitute a point of reference for the management staff in order to design educational programmes at the workplace to strengthen cultural competences of nurses and the quality of the health care provided.